2020
DOI: 10.1038/s41419-020-02820-3
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides targeting lncRNA AC104041.1 induces antitumor activity through Wnt2B/β-catenin pathway in head and neck squamous cell carcinomas

Abstract: Long non-coding RNAs (lncRNAs) contribute to the initiation and progression of various tumors, including head and neck squamous carcinoma (HNSCC), which is a common malignancy with high morbidity and low survival rate. However, the mechanism of lncRNAs in HNSCC tumorigenesis remains largely unexplored. In this work, we identified a novel lncRNA AC104041.1 which is highly upregulated and correlated with poor survival in HNSCC patients. Moreover, AC104041.1 overexpression significantly promoted tumor growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Preliminary studies have shown that Wnt2b is a highly conserved member of the WNT family [48]. Wnt2b was found dysregulated in several cancers with aberrant Wnt/β-catenin pathway activity [49][50][51][52][53]. In our study, we identified that Wnt2b is positively associated with osteogenesis by activating the Wnt/β-catenin signaling pathway for the first time.…”
Section: Discussionsupporting
confidence: 51%
“…Preliminary studies have shown that Wnt2b is a highly conserved member of the WNT family [48]. Wnt2b was found dysregulated in several cancers with aberrant Wnt/β-catenin pathway activity [49][50][51][52][53]. In our study, we identified that Wnt2b is positively associated with osteogenesis by activating the Wnt/β-catenin signaling pathway for the first time.…”
Section: Discussionsupporting
confidence: 51%
“…It has been confirmed that miRNAs could exert their biological function mainly by binding their target mRNAs. 30,31 In the current study, we found cyclin E1 was a direct target of miR-1231, which has been regarded as a key regulator in cell cycle. 32 In addition, CDK2 was found to be downregulated in pancreatic cancer cells in the presence of ABHD11-AS1 shRNA1.…”
Section: Discussionmentioning
confidence: 54%
“…The cell lines may not reflect the actual condition of the cells in the patient's tumor tissue [44]. A feasible strategy to solve this problem is to obtain and use PDCs, and there have been many reports on related studies [45][46][47][48]. Our research not only used three ESCC cell lines, but also established patient-derived cell lines as a supplement.…”
Section: Discussionmentioning
confidence: 99%